Cytokines Gene Expression on Macrophages Exposed to Triatoma Salivary Gland Extracts - Jones, Kenyanna; Montenegro-Cadena, Lidia; Londono-Renteria, Berlin (My University, 2018)
Triatoma sanguisuga and Triatoma Indictiva are vectors of Chagas disease. These two vectors goes to the host and bites down to feed on blood, which is necessary for the egg laying process. The disease however is not spread through their bite, but through their feces. When they become full of blood, they defecate and that is where the parasite is. The parasite is then introduced into the skin when the host scratches at the bite and feces enter the skin. An estimated 8 million people worldwide are infected with T Cruzi, and the United States has the 7th highest prevalence of Chagas infections. The Macrophages produces cytokines including TNF (Tumoral Necrosis Factor), IL-10 and IL-18 in responses to danger or infections, the function include tissue inflammation and destruction.
Keywords: Fall 2018